KEBAHAGIAAN SISWA BOARDING SCHOOL: MENELAAH PERAN PENTING ORIENTASI RELIGIUS DAN KUALITAS PERTEMANAN - Syahrizal Yogi Fahrezi; Tri Na'imah; Nur'aeni Nur'aeni; Retno Dwiyanti (Inteligensi : Jurnal Ilmu Pendidikan, 2024)
This study aims to examine the extent to which religious orientation and friendship quality can influence student happiness at SMP Muhammadiyah Boarding School ‘X’ in Banyumas Regency, Central Java. This study used a quantitative approach to analyse the relationship between variables. Data were collected using the Orientation to Happiness (OTH) scale, Religious Orientation Scale (ROS), and Friendship Qualities Scale (FQS). By applying the Partial Least Square (PLS)-SEM method, the results showed that religious orientation and friendship qualities play a significant role in achieving students' happiness in boarding schools. The findings of this study provide a stronger basis for the development of interventions or programmes aimed at increasing students' happiness in boarding schools. For future researchers, it is recommended to conduct a broader and more comprehensive study involving mediator and moderator variables.